Does the timing of attainment of maturity influence sexual size dimorphism and adult sex ratio in turtles?. (16th April 2014) - Lovich, Jeffrey E.; Gibbons, J. Whitfield; Agha, Mickey
Abstract: The attainment of sexual maturity has been shown to affect measures of sexual size dimorphism (SSD) and adult sex ratios in several groups of vertebrates. Using data for turtles, we tested the model that sex ratios are expected to be male-biased when females are larger than males and female-biased when males are larger than females because of the relationship of each with the attainment of maturity. Our model is based on the premise that the earlier-maturing sex remains smaller, on average throughout life, and predominates numerically unless the sexes are strongly affected by differential mortality, differential emigration, and immigration, or biased primary sex ratios. Based on data for 24 species in seven families, SSD and sex ratios were significantly negatively correlated for most analyses, even after the effect of phylogenetic bias was removed. The analyses provide support for the model that SSD and adult sex ratios are correlated in turtles as a result of simultaneous correlation of each with sexual differences in attainment of maturity (bimaturism). Environmental sex determination provides a possible mechanism for the phenomenon in turtles and some other organisms. © 2014 The Authors. Biological Journal of the Linnean Society published by John Wiley & Sons Ltd on behalf of The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 142–149.